Class - Erich Segal (Toronto Bantam Books, 1995)
From world-renowned author Erich Segal comes a powerful and moving saga of five extraordinary members of the Harvard class of 1958 and the women with whom their lives are intertwined. Their explosive story begins in a time of innocence and spans a turbulent quarter century, culminating in their dramatic twenty-five reunion at which they confront their classmates--and the balance sheet of their own lives. Always at the center; amid the passion, laughter, and glory, stands Harvard--the symbol of who they are and who they will be. They were a generation who made the rules--then broke them--whose glittering successes, heartfelt tragedies, and unbridled ambitions would stun the world.
Keywords: English Fiction